NURSING TECHNOLOGY SUPPORTING FAMILY INVOLVEMENT IN CRITICALLY ILL PATIENTS: A SYSTEMATIC REVIEW - Sumardi, Sulistia Nur; Ismail, Suhartini; Kaloeti, Dian Veronika Sakti (Indonesian Contemporary Nursing Journal (ICON Journal), 2023)
Background: Family involvement in the care of critically ill patients positively impacts treatment outcomes and patient well-being. Nursing technology has become an essential tool in facilitating family engagement   Aims: This study aims to conduct a systematic review of nursing technology that supports family involvement in critically ill patients. Methods: This article utilized a systematic review method. Articles were assessed using the JBI Critical Appraisal Checklist. The instruments were the JBI Critical Appraisal Checklist for Randomized Controlled Trials and the JBI Critical Appraisal Checklist for Cohort Studies. Literature from the past five years was obtained from four databases: Science Direct, Scopus, Springer Link, and ProQuest. Results: Out of 148 articles, 15 were analyzed. Various technologies (such as web-based platforms, tablets, SMS tools, and video conferencing) were used to provide information, enhance decision-making, and provide virtual access to family conferences. Although interventions varied, "Information sharing" and "Activation and participation" were most commonly implemented in the family involvement model. In studies that discussed the components of family involvement more comprehensively, interventions allowed for information adjustment through two-way communication and active family participation in the decision-making process. Conclusion: Based on the findings of this systematic review, it can be concluded that nursing technology has great potential in supporting family involvement in critically ill patients. This technology can significantly improve family well-being, communication, and decision-making. Further research can focus on a deeper understanding of the emotional impact experienced by families of critically ill patients due to the use of technology.